Focusing performance of a multilayer Laue lens with layer placement error described by dynamical diffraction theory. (18th June 2015) - Hu, Lingfei; Chang, Guangcai; Liu, Peng; Zhou, Liang
<x xml:space="preserve">Abstract</x> The multilayer Laue lens (MLL) is essentially a linear zone plate with large aspect ratio, which can theoretically focus hard X‐rays to well below 1 nm with high efficiency when ideal structures are used. However, the focusing performance of a MLL depends heavily on the quality of the layers, especially the layer placement error which always exists in real MLLs. Here, a dynamical modeling approach, based on the coupled wave theory, is proposed to study the focusing performance of a MLL with layer placement error. The result of simulation shows that this method can be applied to various forms of layer placement error.